Career, Private Life, and the Well-Being among College-educated West German Women - Marianna Schaubert (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper describes to what extent college-educatedWest German women manage to reconcile a career and a private life. In addition, it explicitly investigates how the concurrence of career and cohabitation/family/motherhood is linked to women's life satisfaction. I attempt to overcome the difficulties associated with estimating this relation using fixedeffects models. The results suggest that only a small fraction of woman-year observations is categorised as having a career and cohabitation/family/children simultaneously. Considering different birth cohorts and generations of West German women, there are no significant improvements in the reconciliation between career and family. Further, while there are life-satisfaction gains related to both “career” and “cohabitation/family” separately, their interaction terms throughout are negative.
Keywords: D19; J17; J19; 330; Career; Cohabitation; Family; College-educated women; Well-being